Using a supperficially treated 2024 aluminum alloy drill pipe to delay failure during dynamic loading. (October 2019) - Belkacem, Lallia; Abdelbaki, Noureddine; Otegui, Jose Luis; Gaceb, Mohamed; Bettayeb, Mourad
Abstract: For many years, a critical factor while drilling deep wells in Algeria oil fields has been the fatigue loads in drill strings used in high tortuosity sections. One solution is the use of drill pipes made of alternative lighter materials instead of conventional steel. A thorough study of superficially(ST) treated 2024 aluminum alloy joined to steel drill pipes in crooked well trajectories is presented in this article. This work discusses several limiting loads exerted on the drill pipes that affect the drilling operation such as axial, twisting and bending forces, which lead to combined cyclic loads. This study is aimed to determine whether it is possible to extend the drilling operation by joining ST 2024 aluminum alloy drill pipes into the drilling string, without losing drilling stability or reliability. It is established that the ST 2024 aluminum alloy drill pipe exerts significant influence on the allowable combined load, but affects to a larger extent the critical load at which loss of drilling string stability occurs, along with improved resistance to wear and corrosion, even at high temperature. Highlights: Surface treated 2024 aluminum alloy drill pipe has a lower friction coefficient compared to steel drill pipe. Surface treated 2024 aluminum alloy drill pipe has significantly good fatigue resistance even in severe doglegs. The side force in a dog leg region is reduced in aluminum alloy drill string. The mixed drill string assembly provides a balance strength regarding both tensile and bending forces as well as  compression during axial loading.